PENDAMPINGAN IBU HAMIL DI PUSKESMAS KALASAN KABUPATEN SLEMAN YOGYAKARTA - Casnuri, Casnuri; Nurinda, Dewi; Vinanjungsari, Vina (Universitas Respati Yogyakarta, 2021)
Midwifery services are an integral part of health services, to achieve family health in order to achieve a quality family. Midwifery services include individuals, families and communities as an effort to improve, prevent, cure and recover. Midwifery services are provided by midwives in accordance with their authority with the aim of improving the health of mothers and children, in order to achieve a quality, happy and prosperous family.Â The mortality rate in developing countries, about 25-50%, is caused by problems related to pregnancy, childbirth and childbirth. Maternal mortality rate (MMR) is still the government's main concern, both at the central and regional governments. One of the efforts to reduce maternal, infant and under-five mortality rates is by maximizing mentoring for pregnant women. The working area of Puskesmas Kalasan has a target level of maternal health which is also lacking. For this reason, efforts are needed from the health office and health workers in the form of assistance for pregnant women so that the goal is achieved. The mentoring program for pregnant women is a work program aimed at providing assistance, motivation and motivating pregnant women to be diligent in checking their health during pregnancy to the postpartum period. In this program, monitoring is carried out regarding the condition of pregnant women and the fetus they are carrying.Keywords:Â Mentoring, Pregnant Women, Public Health Center.